THE SETTLEMENT FOR SHARIAH ECONOMY DISPUTES WITHIN RELIGIOUS COURT - Ahmad ,SH (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
This research aims to study the application of the article 49 letter (i) of Law No, 3/2006 towardthe Competence of Religious Court within the shariah economy field, to study the settlementmechanism for shariah economy disputes in Religious Court as well as to analyzes theapplication of the article 49 letter (i) of Law No. 3/2006 in Religious Court rulings relating toshariah economy cases. This research uses three (3) approaches; firstly, statute approach is anapproach that studies statutes and regulations relating to the authority of Religious Courts tosettle the shariah economy disputes; second, conceptual approach is an approach that studieslegal concepts and legal experts opinion relating to the syariah economy disputes; and the third,case approach is an approach that studies the religious court’s rulings that have permanent legalpower relating to shariah economy cases. This research comes to conclusion that the article 49letter (i) of Law No. 3/2006 has widely been implemented. The investigation mechanism usingprocedure of general civil law, and the implementation of the article have been introduced to therulings with some constraints and limitation..Keywords : Settlement, Disputes, Economy, Shariah, Religious Court